S=1+2+2^2+2^3+2^4+2^5+2^6+...+2^60
S = 261-1
\(S=\left(2-1\right)\left(1+2+2^2+...+2^{60}\right)\)
\(=2^{61}-1\)
S = 1 + 2 + 22 + 23 + ... + 260
2S = 2 + 22 + 23 + 24 + ... + 261
2S - S = (2 + 22 + 23 + 24 + ... + 261) - (1 + 2 + 22 + 23 + ... + 260)
S = 261 - 1
nếu là tính S thì làm như sau:
S=1+2+2^2+2^3+2^4+2^5+2^6+.....+2^60
=> 2S= 2+2^2+2^3+2^4+2^5+2^6+2^7+....+2^61
=> 2S-S=2^61-1
=> S=2^61-1
S = 1 + 2 + 22 + 23 + ... + 260
2S = 2 + 22 + 23 + 24 + ... + 261
2S - S = (2 + 22 + 23 + 24 + ... + 261) - (1 + 2 + 22 + 23 + ... + 260)
S = 261 - 1